Pengaruh Ragi dan Waktu Fermentasi terhadap Produksi Alkohol Secara Fermentasi Berbahan Baku Gaplek Ubi Kayu (Manihot utillisima) - P. Kianto Atmodjo (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
The research of the ragi and the fermentation time effect on alcohol production by cassava gaplek has been done. The aim of this research were to find out the best time fermentation and trade mark commercial ragi to produce alcohol. Time fermentation were 1 and 2 weeks. The ragi trade marks were NKL and MK. The result showed that the alcohol production was 15-17% in a week, and 18-20% in two week fermentation. The alcohol quantity which produced by both NKL and MK ragi were not significantly different.